THEORETICAL ASPECT OF SOCIO-CULTURAL FUNCTIONS OF SPORTS - Deineko, Alfiia; Krasova, Inna; Marchenkov, Mikhailo (SWorld-Ger Conference proceedings, 2023)
In work, it has been theoretically discovered that sport is part of the structure of a daily marriage, and its varied significance implies the following functions. The sociocultural function of sport is examined, as it manifests itself in the formed devel